A network meta-analysis of the safety of systemic treatments in patients with metastatic hormone-sensitive prostate cancer - Di Maio, Massimo; Gonzalez-Billalabeitia, Enrique; Marandino, Laura; Maroto, Pablo; Timsit, Marc-Olivier; Luccarini, Irene; Robinson, Paul; Van Sanden, Suzy; Hadaschik, Boris A. (Frontiers in Oncology, 2025)
BackgroundThe last decade saw the emergence of several new systemic therapies for metastatic hormone-sensitive prostate cancer (mHSPC). While these treatments demonstrated similar efficacy in indirect comparisons, comparisons of safety outcomes are needed to help guide the selection of treatment regimens and sequences. We conducted network meta-analyses (NMAs) comparing safety of systemic treatments for mHSPC.MethodsA systematic literature review was performed for randomized controlled trials (RCTs) investigating systemic treatments for mHSPC published before July 2022. Studies were restricted by network connectivity and study population homogeneity. Bayesian NMAs were performed for available data on grade ≥3 adverse events (AEs), serious AEs (SAEs), and any AE.ResultsThe study included eight RCTs (n=172–1228 by treatment arm) and seven treatment regimens: androgen deprivation therapy (ADT) alone, docetaxel plus ADT, androgen receptor pathway inhibitor (ARPI; apalutamide, enzalutamide, or abiraterone acetate plus prednisone [AAP]) plus ADT, and docetaxel plus ARPI (darolutamide or AAP) plus ADT. Apalutamide plus ADT had the lowest relative risk ([RR]; 1.18 (95% credible interval [CrI] 1.02–1.35) of grade ≥3 AEs versus ADT alone, followed by enzalutamide plus ADT (1.34 [1.17–1.52]), docetaxel plus ADT (1.44 [1.33–1.56]), AAP plus ADT (1.48 [1.39–1.58]), darolutamide plus docetaxel plus ADT (1.53 [1.33–1.72]), and AAP plus docetaxel plus ADT (1.60 [1.41–1.79]). For SAEs, RRs (95% CrI) versus ADT alone were 1.26 (1.03–1.53) for apalutamide plus ADT, 1.33 (1.12–1.57) for AAP plus ADT, 1.54 (1.28–1.84) for enzalutamide plus ADT, 3.78 (3.35–4.26) for docetaxel plus ADT, and 3.83 (3.39–4.31) for darolutamide plus docetaxel plus ADT. Similar results were observed for any AE.ConclusionsOverall, risk of grade ≥3 AEs, SAEs, and any AE was lower with doublet ARPI versus docetaxel-based doublet or triplet regimens, and apalutamide plus ADT had the lowest risk. Variability of data reporting should be considered.